Statistical evaluation of Low Back Pain Patients in Peshawar District - Ghazala Sahib; Dr. Qamruz Zaman; Saima Aman (Dialogue Social Science Review (DSSR), 2024)
Low Back Pain (LBP) is one of the vastly encountered complaints by physicians all over the world. This study attempts to do statistical evaluation of low back pain patient’s data through three questionnaires in Peshawar district. The data was collected from 300 low back pain patients Khyber Teaching Hospital, Peshawar both from male and female as well as patients belonging to rural and urban regions. The data showed that the female patients of low back pain were suffering more than the male patients, and rural area patients were more complaining than the urban patients. The cronbach alpha for RMDQ, ODI and PSEQ were 0.694, 0.920 and0.724 respectively, means the ODI has the highest reliability. From the Rasch analysis of RMDQ, it is clearly observed that the highest estimate of eta (item difficulty) (strong trait of disability) is for the question "stay in bed because of my back pain”. The other significant items were: "My appetite is not very good because of my back pain", "I walk more slowly than usual because of my back", "I sleep less well because of my back", "Because of my back pain, I get dressed with help from someone else", "I sit down for most of the day because of my back" and "Because of my back pain, I am more irritable and bad tempered with people than usual".